Using a yellow highlighter or not at all: The use of highlighters in enhancing short-term memory - Alftisya, Hutabarat; Wijaya, Grace K.; Gracetia, Maryanto; Klarissa, Santosa; Soenpiet, Marvelia; Himawan, Karel Karsten (Universitas Sarjanawiyata Tamansiswa, 2023)
Recent studies have demonstrated that using colour fonts could enhance memory. However, little is known regarding whether using highlighter would produce a similar effect and, if so, whether the colour of highlighters determine the nuance of effectiveness. This study aims at exploring the effectiveness of the use of highlighters to enhance short-term memory. We chose two colours of highlighters: blue and yellow, with reference to the previous literature. A randomized, matched, one-way ANOVA experimental design was conducted, participated by 97 university students. The result suggests that using yellow highlighter produced the same effect to memory formation as not using highlighter, while using blue highlighter tends to lower the performance of short-term memory formation. The study could potentially inform effective learning strategies to enhance memory performance, especially related to the use of highlighters.